APPLICATION OF GAMES MODELS IN LEARNING INDONESIAN LANGUAGE IN CLASS V PRIMARY SCHOOL (LITERATURE STUDY) - Dina Nurkhakiki, Ade; Nopasari, Dewi (ATTA`DIB, 2025)
Game-based learning models in elementary schools have great potential to improve student learning outcomes. This approach not only facilitates better understanding of the material, but also motivates students to be significant. This research aims to investigate the effectiveness of game-based learning models in improving student learning outcomes in elementary schools, specifically in the context of Indonesian language learning. This research uses a literature study method by collecting secondary data in the form of previous research results that apply a game-based learning model. The data analysis method used is content analysis to explore the effectiveness of various game learning models. The research results show that the application of game learning models such as ESTASI in poetry learning and Teams Games Tournament in thematic learning can significantly improve students' writing skills and their learning outcomes. For example, students who were involved in the ESTASI game showed increased creativity and participation in writing poetry, while students who took part in the Team games Tournament showed an increase in activeness and achievement of learning outcomes. The integration of game learning models in elementary school education promises positive and sustainable results for students' academic development. This approach not only improves students' understanding and skills, but also helps maintain their learning motivation. The implication of this research is the importance of implementing varied and interesting learning models to create an effective and enjoyable learning environment for students at the elementary level.